Selected body temperature in Mexican lizard species - Héctor Gadsden; Sergio Ruiz Gamaliel Castañeda; Rafael A Lara-Resendiz (Global Journal of Ecology - Peertechz Publications, 2018)
Lizards are vertebrate ectotherms, which like other animals maintain their body temperature (Tb) within a relatively narrow range in order to carry out crucial physiological processes during their life cycle. The preferred body temperature (Ts) that a lizard voluntarily selects in a laboratory thermal gradient provides a reasonable estimate of what a lizard would attain in the wild with a minimum of associate costs in absence of constraints for thermoregulation. In this study we evaluated accuracy of modified iButtons to estimate Tb and Ts of three lizard species (Sceloporus poinsettii and Sceloporus jarrovii in northeastern Durango, and Ctenosaura oaxacana in southern Oaxaca, Mexico). We used linear regression models to obtain equations for predicting Tb and Ts of these species from iButtons. Results from regression models showed that TiButton is a good indicator of Tb for S. jarrovii and S. poinsettii during calibration process. In the same way, TiButton is a good indicator of Ts for S. poinsettii, S. jarrovii and C. oaxacana through experimental gradient. Thus, external measurements using modified iButtons provided an accurate measurement of Tb for S. jarrovii and S. poinsettii and Ts for three species of lizards in this study. In laboratory, body temperature (Tb), and preferred temperature (Ts) obtained from S. jarrovii and S. poinsettii fell within the range of Tbs of other lizards in the family Phrynosomatidae. Ts measured for S. jarrovii, S. poinsettii, and C. oaxacana are within the range observed for lizards. Therefore, thermal preferences appear more phylogenetic that certain environmental factors present in each population of lizards of this group.